2008
DOI: 10.1002/pbc.21695
|View full text |Cite
|
Sign up to set email alerts
|

Renal late effects in patients treated for cancer in childhood: A report from the Children's Oncology Group

Abstract: Background Improvements in childhood cancer therapy have led to increasing numbers of long-term survivors. These survivors are at risk for a variety of late effects due to the disease itself, treatment exposures (surgery, chemotherapy, and radiotherapy), underlying medical problems, and health behaviors. The COG LTFU Guidelines are risk-based, exposure-related recommendations for the identification and management of late effects due to therapies utilized in the treatment of childhood cancer, and are designed f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
108
0
10

Year Published

2011
2011
2019
2019

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 127 publications
(120 citation statements)
references
References 85 publications
2
108
0
10
Order By: Relevance
“…Cisplatin, high dose-methotrexate and ifosfamide are all notorious to cause nephrotoxicity. The review article for renal late effects on patients treated for cancer in childhood [4] revealed that ifosfamide may cause permanent and potentially progressive kidney damage. In contrast, it was also described that the outlook for long-term recovery or stability of renal function caused by cisplatin is generally favorable and that methotrexate-induced nephrotoxicity appears to be entirely reversible.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Cisplatin, high dose-methotrexate and ifosfamide are all notorious to cause nephrotoxicity. The review article for renal late effects on patients treated for cancer in childhood [4] revealed that ifosfamide may cause permanent and potentially progressive kidney damage. In contrast, it was also described that the outlook for long-term recovery or stability of renal function caused by cisplatin is generally favorable and that methotrexate-induced nephrotoxicity appears to be entirely reversible.…”
Section: Discussionmentioning
confidence: 99%
“…The most common manifestation of renal toxicity of ifosfamide is proximal tubular dysfunction and less often decreased GFR [4]. A statistically significant fall in mean GFR of 35 mL/min/1.73 m 2 was observed after completion of ifosfamide therapy [6].…”
Section: Discussionmentioning
confidence: 99%
“…For urologists, the prevalence of CKD after radical nephrectomy is a current topic. 4 This study elucidated that CKD develops in testicular cancer survivors after chemotherapy at a relatively high rate. In addition, to assess renal function by the estimated glomerular filtration rate (eGFR), detection and management of factors causing progression of CKD, such as hypertension and proteinuria, are recommended for CKD patients and those with a high risk for CKD.…”
Section: Conflict Of Interestmentioning
confidence: 98%
“…Nephrotoxicity may present as an acute kidney injury, slowly progressing chronic renal disease or dysfunction of the renal tubules. These processes may or may not be reversible [2].…”
Section: Introductionmentioning
confidence: 99%